Kampanye Slow Beauty Skincare di Kalangan Member Female Daily - Situmeang, Sherina Shadewi; Claretta, Dyva (Universitas Prof. Dr. Moestopo (Beragama), 2024)
The concept of slow beauty may be unfamiliar to some, but symbolically, certain skincare practices are interpreted as manifestations of these values. This study aims to explore the form of slow beauty campaigns in skincare among Female Daily members and identify the values of slow beauty being applied. The research employs netnography and a descriptive qualitative approach. Data was collected through online observation in FD Talk